A nitrogén-monoxid szintetáz és a granulocyták szerepe az endotoxin okozta korai miokardiális depresszióban [The role of nitric oxide synthase, and of granulocytes in the endotoxin-induced early myocardial depression] - Wolfárd Antal (MAGYAR SEBÉSZET, 2000)
The aim of our study was to investigate the role of endothelial and inducible nitric oxide synthase (eNOS and iNOS) and granulocytes during hyperdynamic endotoxemia, and to study the cardiovascular effects of the non-selective NOS-inhibitor N-omega-nitro L-arginine methylester (L-NAME) and the selective iNOS-inhibitor mercaptoethylguanidine (MEG) in the early myocardial depression. METHODS: Endotoxemia was induced in anesthetized dogs. Mean arterial pressure, cardiac output and peripheral vascular resistance was monitored, left ventricular contractility was calculated. Myocardial eNOS and iNOS activities and myeloperoxidase (MPO) activity, as the marker of granulocyte infiltration were determined from tissue biopsy samples. RESULTS: Endotoxemia was accompanied by a short hyperdynamic circulatory reaction, hypotension and myocardial depression. We observed an early increase in eNOS and a late increase in iNOS activity. MPO activity increased significantly after 8 hr endotoxemia, suggesting considerable granulocyte-extravasation. Non-selective NOS-inhibition prevented hypotension, exerted positive inotropic effect, but induced a rise in peripheral vascular resistance and a further increase in myocardial MPO activity. MEG treatment stabilized myocardial contractility on the control level, increased cardiac output and attenuated tissue granulocyte infiltration. CONCLUSIONS: The increased activity of eNOS and granulocyte infiltration may be responsible for the early cardiac depression during endotoxemia. Non-selective NOS-inhibition has beneficial effects, but is also induces side-effects by disturbing vasoregulation. Selective iNOS-inhibition has no significant hemodynamic effects during early endotoxemia, but restores cardiac efficacy probably through attenuating granulocyte-associated myocardial dysfunction.